Adsorption measurements on a CrOx/γ-Al2O3 catalyst for parameter reduction in kinetic analysis. (31st July 2016) - Kiedorf, G.; Wolff, T.; Seidel-Morgenstern, A.; Hamel, C.
Abstract: This work presents an attempt to include more detailed descriptions of adsorption equilibria into the analysis of the rates of heterogeneously catalyzed reactions. The adsorption behavior of ethylene, propylene, oxygen, carbon monoxide and carbon dioxide was studied on a CrO x / γ -Al2 O3 catalyst in a broader concentration and temperature range. Dynamic measurements were performed in a tubular reactor applying the Frontal Analysis method, to estimate adsorption isotherms for single components and mixtures individually. The classical Langmuir model and a bi-adsorption model consisting of a Langmuir and a Henry term were parameterized. The temperature dependence of the isotherm model parameters was described via an Arrhenius approach. Using the Multi-Langmuir model and the Ideal Adsorbed Solution Theory, competitive adsorption isotherms for ethylene and propylene were predicted based on the estimated single component parameters. However, the experimental evaluation of the predicted mixture isotherms offered no effect in the concentration range considered. In a higher concentration range the experimental competitive adsorption isotherms were significantly affected. Thus, the considered competitive adsorption models work well. Consequently, the Multi-Langmuir adsorption model is sufficient to describe the investigated model system. With the reliable mathematical description of the adsorption isotherms a more profound description of the reaction rates is possible by separating kinetic and thermodynamic effects. Highlights: Study of the catalytic total oxidation of olefins on CrOx / γ -Al2 O3 catalyst. Analysis of singleand mixture adsorption behavior of C2 H4, C3 H6, O2, CO and CO2 . Langmuir and a bi-adsorption model were parameterized. Olefin mixture was calculated using Multi-Langmuir model and the IAS Theory. Predicted mixture behavior was experimentally validated. Adsorption data can be used to reduce parameter correlations at kinetic analysis.